2018
DOI: 10.3168/jds.2017-14223
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies for tick resistance in Bos taurus × Bos indicus crossbred cattle: A deeper look into this intricate mechanism

Abstract: Rhipicephalus (Boophilus) microplus is the main cattle ectoparasite in tropical areas. Gir × Holstein crossbred cows are well adapted to different production systems in Brazil. In this context, we performed genome-wide association study (GWAS) and post-GWAS analyses for R. microplus resistance in an experimental Gir × Holstein F population. Single nucleotide polymorphisms (SNP) identified in GWAS were used to build gene networks and to investigate the breed of origin for its alleles. Tick artificial infestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 72 publications
(87 reference statements)
1
26
0
1
Order By: Relevance
“…Heterosis effects has immense importance in the performance of crossbreeds in many production systems (Schiermiester et al, 2015;Otto et al, 2018;Prastowo et al, 2021). Although the genetic basis of heterosis is still a subject of investigation, its effect is difficult to quantify.…”
Section: Discussionmentioning
confidence: 99%
“…Heterosis effects has immense importance in the performance of crossbreeds in many production systems (Schiermiester et al, 2015;Otto et al, 2018;Prastowo et al, 2021). Although the genetic basis of heterosis is still a subject of investigation, its effect is difficult to quantify.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, several SNPs in this gene are associated with yearling weight in a tropical composite breed (BovineHD0500013787 on BTA5:47,724,746 explaining 5.35% of the genetic variance and with a − log(P) = 13.7) and with reproductive traits, scrotum circumference and puberty and post-partum anoestrus interval (BovineHD0500013788 on BTA5:47,727,773, explaining 2.50% and 3.87% of genetic variance, respectively, p-value < 10 −7 ) [66,67]. Furthermore, HELB is co-expressed with MYO5A [98,99], which was recently shown to be associated with tick resistance in Bos taurus × Bos indicus crossbred cattle [100]. We also showed that some SNPs are present only in the genome of cattle with indicine ancestry or introgression, including African cattle (indicine as well as taurine) and European 'drought' resistance breeds such as Red Anatolian, or Italian breeds, Marchigiana, Chianina and Piedmontese.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in natural resistance is a consequence of the animals' ability to respond immunologically to tick infestation. Different estimates of heritability for the tick count in cattle are reported in the literature, ranging from 0.12 (aYRES et al, 2014) to 0.54 (oTTo et al, 2018).…”
Section: Feltes Et Almentioning
confidence: 99%